Definição de rotas para coleta porta-a-porta de óleo residual de fritura visando o reuso - Binoto, Renato (Universidade Federal de São Carlos, 2010)
The collection of solid waste generated in urban areas is a growing concern for governments, health professionals and environmentalists. Among these concerns is the disposal of vegetable oil used in homes, which requires a more appropriate final allocation. For this to be attained, it is necessary, in addition to public awareness, the planning for the collection, with pre-defined routes. This study simulates alternative systems to collect waste oil in some sectors of the city of São Carlos SP using a Geographic Information System GIS. Using this system, routes to be travelled by the collectors from door to door, are defined. The program used was the TransCAD, which is a GIS specific for transportation planning, transport professionals, enabling the development routes using algorithms that include a procedure for arc routing. For this study it was assumed that a collector truck would be parked at some defined points and the collection would be performed by collecting agents with carts following pre-defined routes. Several simulations were made, aiming at minimizing the length of the routes and the number of agents necessary for the task. The results obtained with the simulations demonstrated that it is possible to define sets of routes that minimize the cost and the manpower required for the door to door collection of discarded frying oil.
Keywords: Engenharia urbana; Resíduos sólidos; Coleta domiciliar; Roteirização de veículos; SIG, Sistema porta-a-porta; Óleo residual de fritura; Solid waste; Household waste; Vehicle routing; GIS system; Door to door; Residual oil in frying; ENGENHARIAS